Animal Research In Diabetes And Ethical Consideration (Bangladesh Journal of Bioethics, 2012)
Research must have a clear statement that is the hypothesis. This hypothesis may involve a clinical question or pathophysiologic mechanism that cannot be tested ethically or appropriately using human subjects or alternative methods. Therefore, numerous animal models have been developed that mimic to human diabetes. They provide additional knowledge about and insight into disease processes and hopefully better methods for treatment or prevention of diabetes in humans. All scientific research involving the use of animals should begin with an ethical focus by examining the risk-benefit ratio (i.e., morbidity or mortality to the animal versus the potential importance of the knowledge acquired). The aim of this paper is to discuss these ethical aspects within the context of research on diabetes and form a framework for the decision-making process. DOI: http://dx.doi.org/10.3329/bioethics.v1i2.9625 Bangladesh Journal of Bioethics 2010; 1(2): 20-23